Status of Continuous and Comprehensive Evaluation () at Elementary Schools of Khordha District of Odisha - SARANGI, PRABHAT MANJARI (THE PRIMARY TEACHER, 2014)
This paper discusses the status of Continuous and Comprehensive Evaluation in elementary schools of Khordha district, Odisha. A sample of 40 students, teachers and head teachers was selected by using random sampling technique. For collecting data interview schedule, questionnaire and official documents were used. The analysis of data revealed that CCE conducted in elementary schools at Khordha district of Odisha have little influence on all-round growth and development of the learners. Awareness programmes for teachers and effective monitoring mechanism programme are needed to achieve the goal of CCE